PENGARUH MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS XI IPS SMA NEGERI 6 MERANGIN - Irvan Zulvadri; Elvina Safitri (LP3M STKIP Muhammadiyah Muara Bungo, 2019)
This research is motivated by the low level of student motivation which is characterized by a low level of student attendance at school and low student academic learning achievement. The research objective was to determine the effect of learning motivation on student achievement in class XI IPS. The research method used is quantitative with simple linear regression analysis techniques. Research respondents were 102 students of SMA Negeri 6 Merangin. Collecting data that researchers do with questionnaires or questionnaires. The trial of the research instrument is the validity and reliability test. The test for classical assumptions uses normality test and linearity test with the help of SPPS 21 application. The results show that learning motivation has a significant influence on learning achievement shown in the regression coefficient of 0.454 and terminated R Square coefficient 0.640.